THE PRINCIPAL'S STRATEGY IN DEVELOPING EXTRACURRICULAR ACTIVITIES AT MTS TERPADU BERKAH PALANGKA RAYA - Bambang; Musyarafah; Rio Irawan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The strategy of the head of the madrasah at MTs Terkah Berkah Palangka Raya in developing extracurricular activities with the main goal of fostering student development holistically, through extracurricular it is necessary to make commitment efforts that consider the positive and negative impacts. This study aims to describe the strategy for developing extracurricular activities in the Integrated MTs Berkah Palangka Raya. This study uses a descriptive qualitative method using data sources taken from three informants through in-depth interviews, the selected informants are the Head of the Madrasah, the extracurricular coaching teacher, and the students participating extracurricular at the Berkah Integrated MTs. All interview results were then analyzed using data reduction techniques, data presentation, and conclusion drawn. The results of the analysis in this study are: 1) Extracurricular activities at the Berkah Integrated MTs consist of 2 types of groups, namely 5 compulsory extracurriculars and 4 electives with visions, missions and goals that are closely related to the Qur'an. 2) The strategy for developing extracurricular activities at the Integrated MTs Berkah Palangka Raya consists of 3 steps, namely Strategy Formulation by forming a vision, mission and goals. The principal uses SWOT analysis steps to find opportunities, threats, strengths and weaknesses. Followed by the implementation of the strategy, namely forming an extracurricular organizational structure. Ending with Strategic Control in developing extracurricular activities in schools, namely by setting standards, providing performance recognition, making comparisons of work with work standards, and taking corrective actions that can be seen from the weekly, monthly, and attendance reports of each activity that takes place both weekly and monthly.